Isolation of rat hepatic peroxisomes by means of immune free flow electrophoresis - Völkl, Alfred; Mohr, Heribert; Weber, Gerhard; Fahimi, H. Dariush (Electrophoresis, 1997)
Rat hepatic peroxisomes (PO) were separated from other cell organelles by free flow electrophoresis (FFE) in combination with immunocomplexing PO prior to FFE with an antibody directed against the cytoplasmic aspect of the peroxisomal membrane protein PMP 70. This novel approach is based on a method termed antigen-specific electrophoretic cell separation (ASECS) which was originally introduced for the isolation of human T and B lymphocyte subpopulations by Hansen and Hannig (J. Immunol. Methods 1982, 51, 197-208). We adapted this technique to PO isolation from a crude peroxisomal fraction, streamlining it by the following modifications: (i) The sandwich-technique recommended to further lower a negative surface charge was renounced. (ii) Instead, the pH of the electrophoresis buffer was raised from 7.2 to 8.0, thus minimizing the electrophoretic mobility of the particles immunocomplexed due to the fact that the isoelectric point (pI) of IgG molecules is close to pH 8.0. PO isolated by this modification, referred to as immune free flow electrophoresis (IFFE), are as pure, intact, and structurally well-preserved as are highly purified PO obtained by density gradient centrifugation. The technique is currently applied for the isolation of peroxisomal subpopulations that are difficult to obtain by means of density gradient centrifugation Presented at the “Elektrophorese Forum ”︁96” meeting of the German Electrophoresis Society, held at the Technical University Munich, October 23-25, 1996 .